PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Almumtahanah Almumtahanah; Samukri Samukri (STIE Muhammadiyah Jakarta, 2020)
This study raises the issue of the Effect of Application of Accounting Information Systems on the Quality of Financial Statements. The purpose of research conducted by the author is to analyze and obtain empirical evidence of the effect of the application of accounting information systems on the quality of financial statements. The population of this research is the employees of PT. Berkat Sinar Sentosa. The sampling method used in this research is descriptive method. The sample used in this study were 63 employees at PT. Thanks to Sinar Sentosa. The data used are primary data, using SPSS data processing. The results showed that the variable implementation of accounting information systems (X) significantly influence the quality of financial statements (Y). This shows the higher level of application of accounting information systems, the better the quality of accounting financial statements.